Competition between activation energy and migration entropy in lithium ion conduction in superionic NASICON-type Li1−3xGaxZr2(PO4)3. Issue 12 (5th March 2021) - Duan, Shanshan; Huang, Can; Liu, Min; Cao, Zhiwen; Tian, Xiaocong; Hou, Shuen; Li, Jiangyu; Huang, Boyuan; Jin, Hongyun
Abstract : Enhanced prefactor is responsible for the enhanced ionic conductivities in solid state electrolytes, while Ga doping is effective in increasing the migration entropy. Abstract : NASICON-type solid state electrolytes have attracted great interest in all-solid-state batteries, and many attempts have been applied to enhance the ionic conductivity. It is generally believed that low activation energy governs the high ionic conductivity while the prefactor, particularly migration entropy, is often overlooked. Here, employing a combination of electrochemical strain microscopy, speed of sound measurements, and electrochemical impedance spectra, we investigate the structure–property relationships governing ionic conduction behavior in the Li1−3 x Ga x Zr2 (PO4 )3 system. A sharp increase in the prefactor upon Ga substitution is attributed to the increased migration entropy while the increase in activation energy can be rationalized in terms of the inductive effect. These two competitive factors determine the final ionic conductivity.